STYLISTIC CLASSIFICATION OF ENGLISH VOCABULARY - Olimjon Mukhidinovich, Jalilov (PT. Antis International Publisher, 2024)
Objective: By examining several vocabulary kinds (formal, informal, literary, and technical) and their effects on communication efficiency in a variety of contexts, audiences, and goals, this study seeks to understand the significance of stylistic classification in language use. Method: Using a mixed-method approach, the study examines how environmental, social, and cultural factors influence language choice by combining a participant survey, corpus-based analysis, and a literature review. Results: According to the study, literary vocabulary is especially useful for boosting emotional resonance in creative writing, whereas neutral vocabulary is the most adaptable and frequently utilized in both spoken and written communication. Context determines the appropriateness and tone of formal and informal language choices. Although they are essential for accuracy in specialist domains, technical terminology can make things difficult for wider audiences to understand. Furthermore, colloquialisms, euphemisms, neologisms, and dialectal variations enhance language but must be used carefully to prevent misunderstandings. Novelty: By offering a thorough examination of the interactions between vocabulary types and contextual factors, this research advances our understanding of stylistic classifications and provides guidance on how writers and speakers can modify their language to communicate more effectively and clearly in social and professional contexts.